Dynamics of Cereals Production in the States of North Eastern Region of India: An Interstate Comparative Study - Singh, N. Uttam; Das, Kishore K; Roy, A.; Yumnam, Anjoo; Sinha, P. K.; Kumar, Bagish; Tripathi, A. K. (Indian Journal of Hill Farming, 2018)
This paper investigates the temporal variations in area, production and yield of cereals in the states of north eastern India. The study period is from 1966-67 to 2014-15 and it has been divided into five periods: 1966-67 to 1974-75, 1975-76 to 1984-85, 1985-86 to 1994-95, 1995-96 to 2004-05 and 2005-06 to 2014-15 to have an understanding of decadal performance among the states. Growth rate performance of the period 2005-06 to 2014-15 may be regarded as the best among the five study periods. The comparison of production growth rates in all the periods reveals that Nagaland exhibits better performance followed by Arunachal Pradesh. Decomposition analysis reveals that sources of output growth in the states of the region are due to yield improvements (64%) followed by area expansion (36%). Variance analysis depicts that yield varies slowly over each study period with alarge variability among the states suggesting the identifiable state specific factors. Despite area, production and productivity of cereals have shown a steady upward trend in every period of the study the region still has a deficit of 207 thousand tons of cereals against the requirement of the last census year. Though the projected figure of the year 2021 is surplus (0.7%) in the region; if the current scenario continuous, except Arunachal Pradesh, Nagaland and Tripura, all other states of the region will be deficit in cereals requirements in 2021. Considering that cereals are irreplaceable staple of the region and states like Mizoram and Sikkim showing decreasing growth rates in area under cereals during the last decade, the scope of meeting the cereal requirement of the region depend highly on productivity improvement.